Activation of cell adhesion and migration is an early event of platelet-rich plasma (PRP)-dependent stimulation of human adipose-derived stem/stromal cells - Michika, Fukui; Fangyuan, Lai; Masakatsu, Hihara; Toshihito, Mitsui; Yuki, Matsuoka; Zhongxin, Sun; Sakurako, Kunieda; Shigeru, Taketani; Tokifumi, Odaka; Kazu, Okuma; Natsuko, Kakudo (Human Cell, 2024)
Stem cell therapy is a promising treatment in regenerative medicine. Human adipose-derived stem/stromal cells (hASCs), a type of mesenchymal stem cell, are easy to harvest. In plastic and aesthetic surgery, hASC may be applied in the treatment of fat grafting, wound healing, and scar remodeling. Platelet-rich plasma (PRP) contains various growth factors, including platelet-derived growth factor (PDGF), which accelerates wound healing. We previously reported that PRP promotes the proliferation of hASC via multiple signaling pathways, and we evaluated the effect of PRP on the stimulation of hASC adhesion and migration, leading to the proliferation of these cells. When hASCs were treated with PRP, AKT, ERK1/2, paxillin and RhoA were rapidly activated. PRP treatment led to the formation of F-actin stress fibers. Strong signals for integrin β1, paxillin and RhoA at the cell periphery of RPR-treated cells indicated focal adhesion. PRP promoted cell adhesion and movement of hASC, compared with the control group. Imatinib, an inhibitor of the PDGF receptor tyrosine kinase, inhibited the promotion of PRP-dependent cell migration. PDGF treatment of hASCs also stimulated cell adhesion and migration but to a lesser extent than PRP treatment. PRP promoted the adhesion and the migration of hASC, mediated by the activation of AKT in the integrin signaling pathway. PRP treatment was more effective than PDGF treatment in enhancing cell migration. Thus, the ability of PRPs to promote migration of hASC to enhance cell growth is evident.